Cancer biomarkers - Georgakilas, Alexandros G. (Taylor & Francis/CRC Press, 2013)
This unique synthesis of chapters from top experts in their fields, targets the very important and upcoming area of cancer biomarkers and the need for better and more rigorous design and clinical trial. The book covers several aspects of cancer molecular markers from innovation, screening, controversies and future directions. The primary target audience for the book includes PhD and MD students, researchers, biologists, medical doctors and professionals who are interested in mechanistic studies on cancer diagnosis and translational benefits from personalized cancer treatment using the new era of biomarkers.